Does the principal's leadership contribute to teacher job satisfaction at school? - Nellitawati Nellitawati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2019)
The purpose of this study was to analyze the contribution of principals’ leadership to teacher job satisfaction. Using quantitative correlational research methods, which will reveal the contribution of each variable. The research sample was 86 teachers. Data collection used two instruments, namely the teacher's job satisfaction questionnaire and the principal’s leadership questionnaire. Data analysis techniques using simple regression and correlation techniques. The results showed that the principal’s leadership significantly contributed to teacher job satisfaction. It can be concluded that the Principal’s leadership is one of the most important factors because it can affect teacher job satisfaction. So that improving the quality of leadership by school principals needs to be improved.